Erros de prescrição em uma unidade de tratamento intensivo e o papel do Farmacêutico - LUCIANO OLIVEIRA GONÇALVES DA SILVA; Ana Isabel Maia de Oliveira; Ivonete Batsita de Araújo; Valdjane Saldanha (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2019)
Purpose: To evaluate the rate of prescribing errors in the prescribing orders of patients admitted to an intensive care unit (ICU), the medication groups more related to the prescribing errors and the rate of acceptance of pharmacist intervention.  Methods: The prescriptions charts of patients admitted to the ICU of a teaching hospital in Brazil were analyzed. The considered parameters were dose, dosing interval, route of administration, infusion time and dilution of medications. The most common medications related to the errors were also evaluated, as well the acceptance of the interventions made by the pharmacist.  Results: A total of 741 prescriptions charts were analyzed and 480 (64.78%) were included in the study. 374 prescription errors were found after the analysis of 5007 medication orders, which resulted in a error rate of 7.47%. 41.67% of the prescriptions charts had at least one error and the dosing interval error was the most common (35.56% of the errors). The antibiotics were the medications more related to the prescribing errors. The pharmacist made 152 interventions and 98.03% of these were accepted by the physicians.  Conclusion: The prescribing errors are common occurrences in the studied ICU, bringing potential risk to the patients. The dosing interval error was the most frequent type of error found in the study. The systemic antibiotics were the medication group more related to the errors. The acceptance of pharmacist intervention was high.